Spatiotemporal Variations in Surface Heat Loss Imply a Heterogeneous Mantle Cooling History - Krister S. Karlsen; Clinton P. Conrad; Mathew Domeier; Reidar G. Trønnes (Geophysical Research Letters)
Abstract Earth's heat budget is strongly influenced by spatial and temporal variations in surface heat flow caused by plate tectonic cycles. Here, we use a novel set of paleo‐seafloor age grids extending back to the mid‐Paleozoic to infer spatiotemporal variations in surface heat loss. The time‐averaged oceanic heat flow is 36.6 TW, or ∼25% greater than at present‐day. Our thermal budget for the mantle indicates that 149 K/Gyr of cooling occurred over this period, consistent with geochemical estimates of mantle cooling for the past 1 Gyr. Our analysis also suggests sustained rapid cooling of the Pacific mantle hemisphere, which may have cooled ∼50 K more than its African counterpart since 400 Ma. The extra heat released from the Pacific mantle may have been trapped there by the earlier long‐lived supercontinent Rodinia (∼1.1–0.7 Ga), and the Pacific mantle may still be hotter than the African mantle today.